2001
DOI: 10.1016/s1011-1344(01)00258-5
|View full text |Cite
|
Sign up to set email alerts
|

Spectral shade ratios on horizontal and sun normal surfaces for single trees and relatively cloud free sky

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…5) or trees ( e.g. 6,7) attenuate UV radiation. Reflections from urban materials like metals, concrete or glass may enhance radiation to a small extent ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…5) or trees ( e.g. 6,7) attenuate UV radiation. Reflections from urban materials like metals, concrete or glass may enhance radiation to a small extent ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the ground topography on the UV exposures was investigated for inclined planes over high albedo ground surfaces (Weihs, 2002). The UV irradiances on vertical surfaces (Webb et al, 1999) and surfaces normal to the sun have been reported (Parisi and Kimlin, 1999;McKenzie et al, 1997;Parisi et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the levels of UV observed in the shade of different shade environments have shown that the relative proportions of UVA and UVB in the shade are significantly different to those in full sun (Turnbull et al, 2005;Parisi et al, 2001). The relative proportions of the UVA in shade to those in full sun are decreased compared to the relative proportions of the UVB in shade to those in full sun.…”
Section: Discussionmentioning
confidence: 99%